Analysis of the burden of intracerebral hemorrhage in the Asian population aged 45 and older and ARIMA model prediction trends: a systematic study based on the GBD 2021 - Xu, Minghong; Tang, Chao; Shen, Yongkai; Zhang, Yinan; Bao, Long (Frontiers in Neurology, 2025)
BackgroundIntracerebral hemorrhage (ICH), a severe subtype of hemorrhagic stroke, is associated with significant disability and high mortality rates. Due to population aging and the prevalence of hypertension in the Asian region, intracerebral hemorrhage has become one of the major causes of high disability and mortality. This study analyzes the epidemiological patterns of ICH across Asia from 1990 to 2021 and projects potential trends for the period 2022 to 2041.MethodsThis study extracted four key indicators related to intracerebral hemorrhage (ICH) from The Global Burden of Disease (GBD) 2021 database for the years 1990 to 2021: prevalence, incidence, mortality, and disability-adjusted life years (DALYs). The age-period-cohort model was employed to assess the impact of age, time periods, and birth cohorts on ICH trends. Additionally, the autoregressive integrated moving average (ARIMA) model was utilized to conduct long-term trend analysis and forecast the changing trends of various indicators from 2022 to 2041.ResultsFrom 1990 to 2021, age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life-year rate (ASDR) of ICH in Asia exhibited an overall declining trend, the ASIR declined from 82.35 per 100,000 (95% UI: 70.73–93.35) to 52.35 per 100,000 (95% UI: 45.98–58.46). Similarly, the ASMR dropped from 92.02 per 100,000 (95% UI: 83.06–101.24) to 53.26 per 100,000 (95% UI: 47.61–58.96), while the ASDR fell from 2,094.51 per 100,000 (95% UI: 1,916.68–2,293.61) to 1,194.11 per 100,000 (95% UI: 1,072.05–1,306.04). The age effect demonstrated that the relative risk (RR) of ICH increases with age, peaking in the 90–94 age group. The period effect indicated that the risk did not increase over time, while the cohort effect suggested a declining trend in later-born cohorts. The ARIMA model’s predictions indicate that over the next 20 years, the age-standardized rates in Asia, except for prevalence, will generally show a declining trend.ConclusionThe disease burden of ICH in Asia varies by gender and age group. According to ARIMA model predictions, while the overall burden of ICH is expected to decline over the next 20 years, the age-standardized prevalence rate is projected to increase due to population aging. Given the high mortality and disability rates associated with ICH, its disease burden remains significant and requires focused attention. Strengthening screening and hypertension management in high-risk elderly populations, along with community health education and early intervention, is recommended to reduce the risk of ICH.